Analisis Desain Incinerator Pirolysis Fuel Reactor (IPFR) Limbah Plastik Sebagai Bahan Bakar Alternatif - Wahyu Pratama, Aditya; Rofi'i, Ahmad; Afianah, Nuzula; Putri, Salsabila Liandra (Jurnal Teknik Terapan, 2023)
In Indonesia, plastic waste has become an important problem at this time, because it causes environmental pollution problems. With this, further action is needed regarding the treatment of waste utilization, one of which is by converting waste into liquid fuel. Some types of rubbish that we often encounter are plastic bottles such as plastic cups, plastic bottle caps, children's toys and margarines and others, which is one of the types of PP (polypropylene) waste. The development of current plastic waste treatment technology is to convert plastic waste into fuel oil by utilizing plastic waste to be processed as plastic fuels such as premium fuel, diesel and kerosene. Polypropylene type plastic is the type of plastic that is most widely used in daily life because it has good mechanical properties with low density, heat and moisture resistance, and has good dimensional stability. Some of the technology used to convert plastic waste, among others, by using the method of high temperature (Thermal Cracking). In this study, researchers designed a Thermal cracking device, namely an Incinerator, a plastic waste smelter with high temperature, where the modification of this tool is to use used fuel oil or residual oil. In this study, the researcher analyzed the burning time, the amount of waste mass needed for the melting process in the Incinerator. In this research, a fuel equivalent of 1.5 liters of premium fuel was produced with 10 kg of plastic waste burned in the incinerator with a burning time of 125 minutes of the pyrolysis process, with a combustion temperature of 180-250 degrees Celsius.